If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6+9=c
We move all terms to the left:
6+9-(c)=0
We add all the numbers together, and all the variables
-1c+15=0
We move all terms containing c to the left, all other terms to the right
-c=-15
c=-15/-1
c=+15
| -2j=-34 | | (4x)^(-2)(4x)^(3)(4x)^(9)=(4x) | | 72=8(x+9) | | 11w–4=7= | | 2x+10=-44x-7x | | 7y–3=18= | | 6x-3x+4x+x=7x | | –y–1=-2y | | 36/24=x/16 | | 4(3x-5)=30 | | 2x+6=123 | | 10x-9=8x+10 | | 10x-9=8+10 | | 7x=12-13x1-4x13 | | 3+5x=-12+x | | 14=5n=4 | | (x+10)(x+3)-(x+8)(x-1)=(x-2)(x-1)-x^2 | | 18x²+9x=0 | | 4/|h|+12=14 | | 41=15c−4 | | 12x−4=56 | | 5x-10=3x+ | | 3+9x=58 -2x | | 10/30=5/n | | 4x-23=x-27 | | 5t+12=3t+8 | | 2c-10=c+1 | | 10a-2=46 | | (4p-1)/5-(2p+3)/4=p | | 2y+6=8+4y | | 21+32u=36+27u | | 4x-1/3=-7+3/2 |